Climate-driven biogenic emissions alleviate the impact of human-made emission reductions on O3 control in the Pearl River Delta region, southern China - N. Wang; N. Wang; S. Liu; J. Xu; Y. Wang; C. Li; Y. Xie; H. Lu; F. Yang (Atmospheric Chemistry and Physics)
Ozone (O3) concentrations in the Pearl River Delta (PRD) during summer are typically low and often overlooked. However, integrated observational data indicate a consistent increase in summer O3 levels over recent decades (+0.96 ppb yr−1), contradicting China's efforts to reduce anthropogenic emissions. Our dynamically calculated natural emissions show that biogenic volatile organic compound (BVOC) emissions in the region significantly increased between 2001 and 2020, primarily due to climate change and alterations in vegetation cover, with climate-driven BVOC emissions accounting for approximately 80 % of the increase. Furthermore, parallel simulations using the Weather Research and Forecasting–Community Multiscale Air Quality (WRF–CMAQ) model indicate that climate-driven BVOC emissions, by enhancing atmospheric oxidative capacity and accelerating O3 formation, have weakened or even offset the benefits of anthropogenic emission reductions, contributing 6.2 ppb to O3 formation and leading to an unexpected rise in O3 levels. This study enhances our understanding of the mechanisms behind natural emissions in urban O3 formation under climate change and provides insights for future O3 pollution control strategies.